Madness and sanity at the time of Indian independence - Sanjeev Jain; Pratima Murthy; Alok Sarin (Indian Journal of Psychiatry, 2016)
The backdrop of the Indian Independence offers glimpses of many 'metaphors of madness'. In this article, we explore this through a few instances, starting from 1857, around the time of the First War of Independence, to 1947, when India became an independent nation. Such metaphors have their parallels both in historical as well as in contemporary times, where instances of one man's imagination becoming another's concept of irrationality and insanity continue.